Underemployment in China: Causes and Effects - Zhou, Zheng (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The purpose of this paper is to explain the influence factors of matchup and mismatch in the investment of highly educated laborers and income by job for new college graduates in China. Although with the economic development, employment opportunities are constantly increasing, the country has realized the polarization of education with its rapid development in China. A large number of new college graduates flooded the market. The phenomenon is that market labor demand is insufficient to meet the annual supply of new graduates entering the market, resulting in underemployment and overeducation. In China, which is in the process of economic transformation, the more prominent problems in the social labor market are overeducation and a series of mismatches in income returns. This paper has considered the effect of mismatch due to underemployment. Taking this into account, we have used the overlapping generations (OLG) model and found that the greater the mismatch, the greater the underemployment is.